AEMIP robust inversion using maximum phase angle Cole–Cole model re-parameterisation applied for HTEM survey over Lamego gold mine, Quadrilátero Ferrífero, MG, Brazil. Issue 1 (2nd January 2020) - Couto Junior, Marco Antonio; Fiandaca, Gianluca; Maurya, Pradip Kumar; Christiansen, Anders Vest; Porsani, Jorge Luís; Auken, Esben
ABSTRACT: This paper presents the results of airborne electromagnetic induced polarisation inversions using the Maximum Phase Angle (MPA) model for a helicopter time domain survey in the Quadrilátero Ferrífero area, Minas Gerais State (MG), Brazil. The inversions were conducted using a laterally constrained robust scheme, in order to decrease the difficulties to recover the multi-parametric model in a very ill-posed inverse problem, often found in induced polarisation studies. A set of six flight lines over the Lamego gold mine mineralised structure were inverted using the MPA re-parameterisation of the Cole–Cole model and also the classical resistivity-only parameterisation, in order to understand the implications of the induced polarisation effect in the data and, consequently, in the resistivity model. A synthetic study was also conducted, seeking to understand what to expect from the resistivity-only inversions in the real data. According to borehole lithological data and previous structural knowledge from the literature, the results from the Maximum Phase Angle approach indicate an important chargeable body that seems to be in good agreement with a sulfide enriched carbonaceous/graphite and altered mafic unities, which are important markers for the gold mineralisation.